Evaluation of the choice of modeling options in predicting the dynamics of milk prices (Journal of Economic Research & Business Administration, 2019)
Actually, effective activity of enterprises, firms, agriculture production in economy depends howthey can predict and forecasting the future.Activity forecasting of enterprises, firms means evaluation of their development which based on ananalysis of market environment, changes. In market conditions , the role of forecasts increasing for managersof different levels. In that regard ,statistical forecasting methods have become important instrumentfor analytics, marketing activity.Currently, the range of forecasting tasks has expanded. Forecasting is the basis for making managementdecisions and improving the management process. The accuracy and reliability of the forecastresults provides for the identification of the development of socio-economic systems, the study of thepossibility of using existing resources and hidden reserves necessary to improve the efficiency of operationand future development.This article discusses the possibilities of using various modeling options for building final forecasts,as well as topical issues that often arise in forecasting and relating to determining the nature of seasonality,assessing the accuracy and adequacy of the constructed model.The article outlines the significance of trend-seasonal linear type models, based on a comparison oftwo alternative approaches to modeling price movements, reveals the adequacy of the application of alinear model based on chain price indices for milk. In turn, the separation of forecasting methods givenin the study is rather arbitrary, since in practice they are interrelated and complementary.Any forecast estimate necessarily includes elements of extrapolation, modeling and expert opinion.However, for the conditions of operation of any entrepreneurial structure at present, which are characterizedby environmental instability and uncertainty of the future, the most effective, in our opinion,forecasting method – the development of a linear model built on the basis of chain indices of milk prices,was identified.